Eriophyid mite Floracarus perrepae readily colonizes recovering invasive vine Lygodium microphyllum following herbicide treatment - Aaron S. David; Jonathan S. Glueckert; Stephen F. Enloe; Andrea Carmona Cortes; Anwar A. Abdel-Kader; Ellen C. Lake (BioControl, 2021)

Potential inter-guild interactions to enhance biological control of Bactericera cockerelli on tomatoes: a laboratory and cage study - Emiliano R. Veronesi; Oluwashola Olaniyan; Howard London; David J. Saville; Stephen D. Wratten (BioControl, 2021)

Implementation of access and benefit-sharing measures has consequences for classical biological control of weeds - Luciana Silvestri; Alejandro Sosa; Fernando Mc Kay; Marcelo Diniz Vitorino; Martin Hill; Costas Zachariades; Stephen Hight; Philip Weyl; David Smith; Djamila Djeddour; Peter G. Mason (BioControl, 2020)
The Convention on Biological Diversity and the Nagoya Protocol establish that genetic resources shall be accessed only upon the existence of prior informed consent of the country that provides those resources and that benefits arising from their utilization shall be shared. Pursuant to both agreements several countries have adopted regulations on access and benefit-sharing. These regulations have created a challenging obstacle to classical biological control of weeds. This paper reviews the experiences of Argentina, Brazil, South Africa, the USA, Canada and CABI in implementing access and benefit-sharing regulations and the implications these measures have on the effective and efficient access, exchange and utilization of biological control agents. We conclude that policy makers should be made aware of the key role biological control plays for agriculture and the environment and they are encouraged to develop tailored access and benefit-sharing legal frameworks that facilitate biological control research and implementation.

Molecular identification of Botryosphaeria dothidea as a fungal associate of the gall midge Asphondylia prosopidis on mesquite in the United States - Ikju Park; Soum Sanogo; Stephen F. Hanson; David C. Thompson (BioControl, 2019)